Contributions of Iberian Foundations to the Achievement of Global Goals - Fialho, Ana (2019)
In this paper we analyse the contribution of two Iberian Foundations to the United Nations SDGs (Global Goals). In particular, we studied, the case of Eugénio de Almeida Foundation, from Portugal, and Yuste Foundation, from Spain, between 2016 and 2018. To achieve the main objective, three specific objectives were defined: the first one is to understand if sustainability is present in the Foundations Mission, Vision and Values; the second one is to analyse how the activities developed by each Foundations contribute to the SDGs and relate these activities to the SDGs targets; and finally to do a comparative analysis of the results of the two foundations. To reach these objectives, we use the case study method based on the analysis of annual reports and websites of the two Foundations and cross-referenced information about the mission, objectives, values and activities developed since 2016 with the specific targets of Global Goals. This paper show that Iberian Foundations contribute to the sustainable development goals, since its mission fits perfectly with the objectives for sustainable development as its activities have a strong social nature and aim at sustainable development in the regions where they operate and beyond. However, we do not find it easily because the Foundations do not provide sustainability reports, nor do they provide sustainability information in their annual reports and accounts, or on their web sites. The study will present contributions at several levels: literature, policy and practice. It makes contributions to the literature on relationships between sustainability practices and sustainability report; the regulation and institutionalization of sustainability practices and reporting for SDGs. Also, it contributes to a better understanding of the role of Iberian Foundations as partnerships for global goals and their contribution to the effective develop, accountable and transparent institutions at all levels.